2007
DOI: 10.1007/s11695-007-9089-z
|View full text |Cite
|
Sign up to set email alerts
|

An Assay to Measure Angiogenesis in Human Fat Tissue

Abstract: This angiogenesis assay based on human fat tissue uses three-dimensionally intact human tissue. The vessels are derived from quiescient vessels within the fat. These properties allow the angiogenic switch to be evaluated in an in vitro setting. The angiogenic response of fat tissue is not identical to placental tissue. This assay allows exploration of angiogenesis in fat tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Early studies described a stimulation of angiogenesis by adipose tissue in animal models, such as grafts of rabbit adipose tissue onto cornea (13) or onto the brain surface (14). A more recent study showed de novo formation of vessels from human adipose tissue embedded in fibrin thrombin clot (25). The adipose tissue samples that we obtained from obese subjects induced a powerful angiogenic response when layered on CAM, a well-known and robust model of angiogenesis (27).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Early studies described a stimulation of angiogenesis by adipose tissue in animal models, such as grafts of rabbit adipose tissue onto cornea (13) or onto the brain surface (14). A more recent study showed de novo formation of vessels from human adipose tissue embedded in fibrin thrombin clot (25). The adipose tissue samples that we obtained from obese subjects induced a powerful angiogenic response when layered on CAM, a well-known and robust model of angiogenesis (27).…”
Section: Discussionmentioning
confidence: 78%
“…Hypoxia and inflammation strongly promote angiogenesis (2,3,25,32). It was shown in mice that oxygen supply is decreased in hypertrophic adipose tissue (41), and expression and macrophage density of cytokines in adipose tissue are increased in obesity (37,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Subcutaneous adipose tissue was removed from the anterior abdominal area of morbidly obese subjects undergoing gastric bypass surgery through the incisions placed to insert the laparoscopic instruments. The fat was placed directly into sterile assay media (see below), transported directly to the laboratory from the surgery in the sterile container and processed under a laminar flow hood.…”
Section: Methodsmentioning
confidence: 99%
“…The angiogenesis media were replaced every 48 h and appropriate concentrations of fresh enterostatin were added. Wells were evaluated for the angiogenic response as described by Greenway et al 18 An observer unbiased to the treatment protocols evaluated the angiogenic response using a semi-quantitative visual rating scale. 19 Essentially, the tissue was viewed under an inverted microscope, visually divided into four quadrants and each quadrant was given a numeric score from 0 to 4 based on the neovessel's length, density and percentage of the quadrants' circumference involved with the angiogenic response.…”
Section: Methodsmentioning
confidence: 99%